From Values to Practices: Unveiling the Dynamics of Organizational Culture in the Implementation of Green HRM in Semarang Hotels - Utami , Aprilia Prehesti; Palupiningtyas, Dyah (International Journal of Economic, Finance and Business Statistics, 2024)
This study explores the role of organizational culture in supporting the implementation of Green Human Resource Management (GHRM) in the hotel industry in Semarang City, Indonesia. Using an ethnographic approach, this research reveals how cultural factors, such as sustainability values, leadership support, employee involvement, organizational learning, and reward systems, shape and support GHRM practices. The findings indicate that an organizational culture aligned with GHRM objectives facilitates more effective and sustainable implementation. However, this study also uncovers the dynamics and challenges in aligning organizational culture with GHRM, such as resistance to change and the paradox between sustainability goals and business priorities. This research contributes to the literature by providing contextual understanding of the role of organizational culture in GHRM and offers recommendations for hotel managers in creating a culture conducive to sustainability through GHRM.